(untitled) (Nonconventional Technologies Review, 2023)
Experimentally, fine porosity-aerated concrete was made using the technique of corrosion the aluminum powder as a foaming agent in Ca(OH)2 solution. The powder (below 10 μm) was obtained from recycled waste, melted by microwave irradiation and atomized by the contact with gaseous nitrogen jets in an original facility designed by authors. The making recipe of concrete is based on calcined gypsum as the main binding agent substituting the pollutant and non-economic cement, fly ash from industrial coal burning, perlite, silica fume, hydrated lime and distilled water. Aerated concrete with excellent thermal insulation properties (density of 601 kg/m3, heat conductivity of 0.114 W/mK, and porosity of 75.2 %) was obtained. The compression strength was increased to 3.9 MPa by curing process with 0.3 bars-steam and 75 ºC for 4 hours and holding further 8 hours inside a sealed room heated to 80 ºC. The product belongs to the new generation of building materials made without CO2 emission and with low energy consumption.